KARAKTERISTIK PROGRAM KURIKULUM PONDOK PESANTREN - Sadiah Rahmawati (Al-Mau'izhoh, 2020)
The curriculum program has not been neatly administered in the form of pesantren document archives. Pesantren document administration guidelines are not yet owned by the boarding school administrators in the field of curriculum. This study aims to uncover the characteristics of curriculum programs including; the objectives, program structure, typology, implementation and evaluation of the curriculum in the Pondok Pesantren Al-Muawanah Cileunyi, Indonesia. The research method used is a qualitative research with a descriptive approach. Data collection techniques used were interviews with leaders of Islamic boarding schools, religious teachers and students, observation includes learning activities, religious teacher meetings with scholars and curriculum program documentation, learning process. The validity of the data in this study uses triangulation of data sources. The results showed that; first, the purpose of the curriculum program is to improve the ability of students in science and Islam; secondly, the curriculum program includes learning activities for santri, pesantren kilat with the third community, learning processes using bandongan and arrogant methods; fourth, evaluation of learning through written and oral tests; fifth, the typology of pesantren is salafiyah.